2010
DOI: 10.1007/s10620-010-1418-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Flora Are Associated with Septic Complications and Death in Critically Ill Patients with Systemic Inflammatory Response Syndrome

Abstract: BackgroundGut under severe insult is considered to have an important role in promoting infection and multiple organ dysfunction syndrome from the viewpoint of altered intestinal epithelium, immune system and commensal bacteria. There are few reports, however, about the relationship between gut flora and septic complications.MethodsWe analyzed gut flora in patients with systemic inflammatory response syndrome (SIRS) and evaluated key bacteria and their cutoff values for infectious complications and mortality by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
160
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 23 publications
3
160
0
4
Order By: Relevance
“…This Janus-faced characteristic of the gut microbiota resembles the immune system itself, a powerful defense that can turn on its host. Altered gut microflora is involved in the pathogenesis of a wide variety of diseases, including metabolic syndrome, obesity, congestive heart failure, pancreatitis, inflammatory bowel disease, and critical illness [1][2][3][4]. As Hayakawa et al point out in this issue of Digestive Diseases and Sciences, the gut microbiota is also dramatically changed in acute trauma, out-of-hospital cardiac arrest, and cerebrovascular disease [5].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This Janus-faced characteristic of the gut microbiota resembles the immune system itself, a powerful defense that can turn on its host. Altered gut microflora is involved in the pathogenesis of a wide variety of diseases, including metabolic syndrome, obesity, congestive heart failure, pancreatitis, inflammatory bowel disease, and critical illness [1][2][3][4]. As Hayakawa et al point out in this issue of Digestive Diseases and Sciences, the gut microbiota is also dramatically changed in acute trauma, out-of-hospital cardiac arrest, and cerebrovascular disease [5].…”
mentioning
confidence: 99%
“…Most studies of gut microbiota in critical illness have examined hospitalized patients receiving intensive care [4,6]. Shimizu et al have shown that the gut microbiota is significantly altered in patients with systemic inflammatory response syndrome (SIRS) [4,6].…”
mentioning
confidence: 99%
See 3 more Smart Citations